Methods of translating introduction and section labels at Vietnam Museum of Ethnology = Phương pháp dịch bảng chú thích tại bảo tàng dân tộc học - An, Minh Khôi (2021)
Translation for descriptive labels at various tourist sites has always been a challenge for students of language due to the level of terminology and cultural knowledge. In this research, methods of translating introduction and section labels at Vietnam Museum of Ethonology were studied based on theories on translation methods. The purpose of this research is to find out the most common translation methods used in translating these labels and suggestions for their translations. 57 indoor labels were collected and transcribed for the purpose of investigation. The researcher found out that four methods were being applied: communicative translation, free translation, semantic translation, and faithful translation. Based on the analysis, the most used method is communicative. For further studies, it is recommended that combination of methods and scope of study should be expanded